Analysis of Presupposition in English Teaching Materials at SMAN 4 Palu - Zulfikri, Zulfikri (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2024)
This study aims to analyze the types of presuppositions in English teaching materials at SMAN 4 Palu. The method used in this research is discourse analysis of the English textbooks used in the eleventh grade, focusing on identifying examples of existential, factual, and structural presuppositions. Data were collected through critical discourse analysis techniques and interviews. The results of the analysis show that the teaching material at SMAN 4 Palu contains various types of presuppositions that can influence students' understanding. Existential presuppositions, such as "The President of the United States," assume knowledge about a particular entity, whereas factual presuppositions, such as "John stopped smoking," assume the truth of information that students may not know. Structural presuppositions, for example, the use of the word "again" in "He came back again," involve hidden assumptions that require contextual background for proper understanding. Findings show that teaching materials often contain presuppositions that are not relevant to students' local contexts, such as the use of examples from Western culture that students may be unfamiliar with. Therefore, adapting teaching materials to local contexts is very necessary. This research recommends the involvement of Palu regional teachers and education experts in curriculum development and the adaptation of teaching materials to make them more relevant to students' daily lives. By integrating local culture into teaching, students' understanding of texts can increase significantly, enhancing learning effectiveness and supporting the achievement of optimal learning outcomes.